2003
DOI: 10.1111/j.2042-7158.2003.tb02433.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of route of administration on the absorption and disposition of α,- γ- and δ-tocotrienols in rats

Abstract: A study was conducted to evaluate the bioavailability of alpha-, gamma- and delta-tocotrienols administered via oral, intravenous, intramuscular and intraperitoneal routes in rats. Three separate experiments, each conducted according to a two-way crossover design, were carried out to compare intravenous and oral, intramuscular and oral, and intraperitoneal and oral administration. Oral absorption of all three tocotrienols was found to be incomplete. Of the three tocotrienols, alpha-tocotrienol had the highest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
94
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(98 citation statements)
references
References 13 publications
2
94
2
Order By: Relevance
“…Moreover, the distribution of the TCT isomers at the time of their maximal plasma concentrations reflects the percentage distribution of TCT in the palm oil TRF supplement. This result suggests that in dogs, the intestinal absorption rate is not different among a-, b-, g-and d-TCT, which seems to be the same situation as in human subjects (12 -14) , but it is in contrast to rats, in which a-TCT is absorbed preferentially compared with g-and d-TCT (15,16) .…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Moreover, the distribution of the TCT isomers at the time of their maximal plasma concentrations reflects the percentage distribution of TCT in the palm oil TRF supplement. This result suggests that in dogs, the intestinal absorption rate is not different among a-, b-, g-and d-TCT, which seems to be the same situation as in human subjects (12 -14) , but it is in contrast to rats, in which a-TCT is absorbed preferentially compared with g-and d-TCT (15,16) .…”
Section: Discussionmentioning
confidence: 84%
“…Moreover, the distribution of the TCT isomers at the time of their maximal plasma concentrations reflects the percentage distribution of TCT in the palm oil TRF supplement. This result suggests that in dogs, the intestinal absorption rate is not different among a-, b-, g-and d-TCT, which seems to be the same situation as in human subjects (12 -14) , but it is in contrast to rats, in which a-TCT is absorbed preferentially compared with g-and d-TCT (15,16) .In the present study, a-TCP was the major vitamin E isomer in plasma, even when dogs were challenged with a preparation whose composition was high (75 %) in TCT. This finding is in agreement with previous studies that examined the effect of TCT supplementation in human subjects (12,14,17) and might be due to a rapid replacement of a-TCP in plasma lipoproteins by newly absorbed a-TCP from the gut (18) .…”
mentioning
confidence: 86%
“…While the absorption mechanisms are fundamentally similar for all vitamin E compounds, tocotrienols are reported to be absorbed in the digestive tract, incorporated into chylomicrons, and transported in the lymphatic system. It has been reported to be absorbed preferentially into human liver carcinoma (HepG2) cells and degraded to a greater amount (Birringer et al 2002;Yap et al 2003). On the other hand, the bioavailability of orally taken tocotrienols is relatively inferior to that of a-tocopherol (Sen et al 2006).…”
Section: Bioavailability Of Tocotrienolsmentioning
confidence: 99%
“…Some studies reported that tocotrienols exert more potent anti-cancer activity compared to tocopherols (Pierpaoli et al, 2010;Hiura et al, 2009;Takahashi and Loo, 2004). However, low absorption due to its poor water solubility and shorter half-life of tocotrienols compared to tocopherols has greatly hindered their therapeutic action especially when administered orally (Compadre et al, 2014;Yap et al, 2003).…”
mentioning
confidence: 99%